2016
DOI: 10.1128/jvi.01697-16
|View full text |Cite
|
Sign up to set email alerts
|

The Coat Protein and NIa Protease of Two Potyviridae Family Members Independently Confer Superinfection Exclusion

Abstract: Superinfection exclusion (SIE) is an antagonistic virus-virus interaction whereby initial infection by one virus prevents subsequent infection by closely related viruses. Although SIE has been described in diverse viruses infecting plants, humans, and animals, its mechanisms, including involvement of specific viral determinants, are just beginning to be elucidated. In this study, SIE determinants encoded by two economically important wheat viruses, Wheat streak mosaic virus (WSMV; genus Tritimovirus, family Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 79 publications
(105 reference statements)
2
29
0
Order By: Relevance
“…However, high expression of either N or RdRp results in cell death and cause negative effects on the replication and transcription of TSWV. Moreover, ectopic expression of N and RdRp by the strong 35S promoter also seems to cause superinfection exclusion, as earlier observed and reported with various viruses infecting humans, animals, and plants (47, 5860). During superinfection exclusion a preexisting infection of virus prevents a secondary infection with the same or a highly similar virus.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, high expression of either N or RdRp results in cell death and cause negative effects on the replication and transcription of TSWV. Moreover, ectopic expression of N and RdRp by the strong 35S promoter also seems to cause superinfection exclusion, as earlier observed and reported with various viruses infecting humans, animals, and plants (47, 5860). During superinfection exclusion a preexisting infection of virus prevents a secondary infection with the same or a highly similar virus.…”
Section: Discussionsupporting
confidence: 75%
“…It is an active virus-controlled process that may be determined by a specific viral protein. For example, for potyvirus the coat protein and NIa protease have been identified to control superinfection exclusion (60). For TCV, the p28, involved in replication protein, was shown to confer superinfection exclusion as a priori expression of p28 blocked (re-)infection with TCV (47).…”
Section: Discussionmentioning
confidence: 99%
“…The very fact that the each of the cell clusters contained a single variant betrays highly stringent population bottlenecks that permitted just one variant to infect a group of connected cells in an SL. Strikingly similar observations have since been made with other viruses, including WSMV, apple latent spherical virus (ALSV), tobacco etch virus (TEV), and a negative-strand RNA virus known as sonchus yellow net virus (SYNV) [29][30][31][32][33] , underlining the highly conserved nature of intracellular bottlenecking encountered by virus populations.…”
Section: Do Natural Viral Infections Entail the Entry Of Large Numbermentioning
confidence: 56%
“…It is also well known that established infections exclude secondary invasions by the same virus 7,[38][39][40] . Finally, such exclusion/repression has been shown to be actively enforced by virus-encoded proteins in several cases 30,31,34 . Why would viruses actively block most copies of their own genomes from replicating in the same cell?…”
Section: Why Do Viruses Bottleneck Their Own Populations Inside the Cmentioning
confidence: 99%
“…For example, when GFP-and RFP-labeled plum pox virus derivatives were coinoculated onto plants, the fluorescent markers demonstrated that the two viruses coexisted in the same plant leaves but showed that they occupied largely nonoverlapping cell clusters (26). Similar spatial separation or mutual exclusion between variants of the same virus have been observed for apple latent spherical virus and bean yellow mosaic virus (27,28), TMV (29,30), soilborne wheat mosaic virus (31), wheat streak mosaic virus (WSMV) and Triticum mosaic virus (TriMV) (32), and turnip crinkle virus (TCV) (33). However, when these differently tagged viruses were inoculated sequentially, the primary virus infection completely blocked subsequent infection by the secondary invader at the whole-plant level (34)(35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 65%